Gender differences in sexual satisfaction through network analysis in young cisgender peruvians - Susana K. Lingán-Huamán; José Ventura-León; Alma Ruiz-Hernández; Ariadna Campana-Tanta (Scientific Reports)
Abstract Gender differences related to sexual satisfaction (SS) have been discussed for decades. However, these subtle differences in SS indicators and their associations have not been fully understood. This study aims to analyze differences in the network structures of the items of an SS scale between men and women. The participants included 205 men (M_age = 21.6 ± 2.13) and 219 women (M_age = 22.1 ± 2.21) from Peru. Using network analysis, we identified the central elements in young men and women and compared the network structures based on gender. Results showed that “concentration during sexual activity” is an important and characteristic aspect of men’s SS, whereas “variety of sexual activities” is the most relevant aspect for women to perceive themselves as sexually satisfied. Differences and similarities in the elements that contribute to SS are described for males and females, highlighting that strategies designed to promote SS for both groups should take these into account.